GAME-BASED LEARNING IN SINGAPORE HIGHER EDUCATION – A PILOT STUDY - Tham, Raymond; Tham, Lesley (PEOPLE: International Journal of Social Sciences, 2015)
Today’s IT-savvy students are accustomed to multi-tasking, graphics, fun, and fantasy. They are said to have short attention span. Educators are finding it challenging to engage and motivate students with the traditional mode of teaching. They are increasingly seeking to tap the potential of game-based learning to engage and motivate learners. Game-based learning is also catching on in schools and higher education in Asia. Universities in Singapore are beginning to explore new ways to engage students in learning. This paper examines whether game-based learning is an effective instructional strategy for engaging students in higher education in Singapore. It will examine how game-based learning motivates and engages students and whether game-based learning is an effective instructional strategy for engaging students in higher education in Singapore.